Motives for Participating in the Religious Experience - Gorlow, Leon (Journal for the scientific study of religion, 1968)
A more or less exhaustive set of reasons for participating in religious activities was identified by respondents from a wide variety of religious denominations. These reasons were cast into a standard form and presented as a Q-sort to 100 undergraduates who rated each reason's "importance to me." A principal components inverse factor analysis yielded seven interpretable clusters of people (types): the humble servants of God; the self-improvers; the family guidance seekers; the moralists; the God-seekers; the socially-oriented servants of God; the religious eggheads. These clusters correspond to dimensions found in other studies. Degree of membership in clusters related meaningfully to personal, social and demographic variables.